Molecular modelling and gene expression analysis to probe the GT-γ trihelix transcription factors in Solanum tuberosum under drought stress - Tayyaba Bint Tariq; Faiza Munir; Ishrat Jabeen; Alvina Gul; Rabia Amir (Scientific Reports)
Abstract GT-γ transcription factors, a subfamily known for their involvement in stress responses, remain uncharacterized in Solanum tuberosum under drought stress. This study employed in-silico approaches and in-vitro expression profiling in differential tissues to investigate StGTγ-1, StGTγ-2, StGTγ-3, and StGTγ-4 potential role in the potato’s drought tolerance mechanisms. Analysis of cis-regulatory elements showed complex networks controlling stress response. Alpha helices were prevalent in their structures, possibly aiding protein stability and interaction. Additionally, intrinsically disordered regions were observed in some StGT-γ proteins, suggesting their role in stress adaptation through flexibility. Protein structure modeling and validation revealed structural diversity within the GT-γ family, potentially reflecting variations in functionalities. Physicochemical analysis highlighted differences in protein properties that could influence their nuclear function. Post-translational modifications further diversified their functionalities. Subcellular localization prediction and topology analysis confirmed their nuclear localization, aligning with the anticipated role in transcriptional regulation. GT-γ proteins likely regulate genes due to structural variations. This is based on the presence of DNA-binding domains and functional annotation suggesting roles in metabolism, gene expression, and stress response. Molecular docking predicted partners involved in drought response, indicating GT-γ proteins’ role in drought tolerance networks. Identified StGT-γ genes were highly expressed in leaves after 14 days of drought stress, indicating their key role in protecting this vulnerable tissue during drought. This study enhances understanding of GT-γ factors and provides a foundation for the functional characterization and in-depth exploration of the role and regulatory mechanisms of GT-γ genes in potato’s response to drought stress.